KOMBINASI KITOSAN DAN Lactobacillus acidophilus SEBAGAI ANTIBAKTERI Escherichia coli - Febriyani, Erisa; Yusneli, Yusneli; Siregar, Sri Sulpha; Handayani, Handayani; Afriayani, Iis (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2024)
ABSTRACT Background: Chitosan is a prebiotic obtained from fishery waste raw materials such as shrimp heads and crab shells which are abundant in Indonesia. Prebiotics are indigestible ingredients that produce beneficial effects on the host by selectively stimulating the growth of one or more specific bacteria. LAB from the genera Lactobacillus and Bifidobacterium have potential as probiotic agents that are beneficial for human and animal health. The amount of probiotics can be optimized by using prebiotics. The synergistic concept between probiotics and prebiotics is known as synbiotics. This research aims to see the effect of the combination of chitosan and Lactobacillus acidophilus on the growth of Escherichia coli bacteria in Vivo. Methods: E. coli in cecum duck was determinant by plate count method. Results: The average of E. coli content in the cecum of pegagan duck were : 40.00; 78.33; 21.67; 19.33 dan 11.00x105 CFU/mL for treatment A (control), B, C, D, E, F, G, and H respectively. Conclusion: The results showed that the treatment had significant effect (P<0,05) on E. coli. Keywords : L. acidophilus sp, Chitosan 0,2%, E. coli